Mengelola Perubahan dalam Pendidikan Islam - Tanjung, Titony; Jamilus, Jamilus (AHKAM, 2023)
Managing change in Islamic education is essential to ensure religious education is relevant, effective, and meets the needs of the times. Here are some steps that can be taken to manage change in Islamic education. Needs analysis, stakeholder engagement, curriculum renewal, professional development, use of technology, evaluation and assessment, inter-agency collaboration, effective communication, and openness to change. In this study, we used a type/research approach in the form of library research. Researchers use descriptive research methods because they are in accordance with the problems studied. the rapid development of the times, especially in the field of education, takes place continuously so that it is inevitable that the education system in the future will experience changes. This shows that change is critical to managing Islamic education because educational attainment is always changing and is not limited by time or geography.